Epidemiologia e serviços de saúde Epidemiology and health services - Moisés Goldbaum (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1996)
A aplicação crescente da metodologia epidemiológica no campo médico-sanitário consolida os seus usos em serviços de saúde. Embora de implementação ainda precária, a legitimação de quatro de seus usos, na análise de situação de saúde, na vigilância epidemiológica, nos estudos etiológicos e na avaliação de serviços, programas e tecnologias consagra-se na Lei Orgânica de Saúde brasileira. A sua atuação no eixo político-institucional e no plano operacional, se devidamente implementada, permitirá fornecer importantes subsídios para os serviços na condução de suas atividades. The growing application of epidemiological investigation to the health and medical field has consolidated its various uses in health care services. Brazilian legislation now provides back-up for four different types of applications, although their implementation is still precarious: analysis of the health situation, epidemiological surveillance, etiological studies, and evaluation of health care services, programs, and technologies. Proper deployment of such epidemiological applications on both the political/institutional and operational levels will provide relevant subsidies for health services in conducting their activities.